Write2Gether and Write2Flourish talk series / Dr. Aisyah Hasyila Jahidin and Associate Prof. Dr. Mahmathi Karuppannan - Jahidin, Aisyah Hasyila; Karuppannan, Mahmathi (Faculty of Pharmacy, 2023)
On July 24, 2023, the Faculty of Pharmacy conducted Write2Gether & Write2Flourish Talk Series under the strategic initiative, Promoting Impactful Publication from Academics (PROLIFIC). It is a part of an ongoing effort by the faculty to boost the publication output of faculty members by focusing on high-quality publications. . The event kicked off with a hands-on workshop in the morning by Assoc. Prof. Dr. Syed Adnan Ali Shah. This workshop aimed to equip participants with the necessary knowledge and expertise to enhance their academic writing processes through the effective utilisation of artificial intelligence (AI) tools. During this workshop, the participants were taught on how to apply AI tools to produce high-quality academic writing more swiftly and easily. The workshop highlighted several tools, namely QuillBot, Wordtune, Humata, Elicit, and ZeroGPT.